Does Rh Immune Globulin Suppress HLA Sensitization in Pregnancy? - Kaufman, Richard M. (2012)
BACKGROUND: How Rh immune globulin (RhIG) prevents sensitization to D antigen is unclear. If RhIG Fc delivers a nonspecific immunosuppressive signal, then RhIG may inhibit sensitization to antigens other than D. HLA antibody prevalence was compared in previously pregnant RhD negative versus RhD positive women to investigate whether RhIG suppresses HLA sensitization. STUDY DESIGN AND METHODS: In the Leukocyte Antibody Prevalence Study (LAPS)(1), 7,920 volunteer blood donors were screened for anti-HLA antibodies and surveyed about prior pregnancies and transfusions. A secondary analysis of the LAPS database was performed. RESULTS: RhD negative women ≤40 years old (presumed to have received antenatal ± postpartum RhIG in all pregnancies) had a significantly lower HLA sensitization rate than RhD positive women (RR 0.58, 95% CI 0.40–0.83). When stratified by deliveries (1, 2, 3, or ≥4), RhD negative women ≤40 were HLA sensitized less often than RhD positive women in every case. In contrast, a clear relationship between RhD type and HLA sensitization was not seen in older previously pregnant women whose childbearing years are presumed to have preceded the use of routine RhIG prophylaxis. In a multivariable logistic regression model, RhD negative women ≤40 years old remained significantly less likely to be HLA sensitized compared with RhD positive women after adjusting for parity, time from last pregnancy, lost pregnancies, and transfusions (OR 0.55, 95% CI 0.34–0.88). CONCLUSION: Consistent with a nonspecific immunosuppressive effect of RhIG, younger previously pregnant RhD negative women were less likely than previously pregnant RhD positive women to be HLA sensitized.